Genome Reports: Contracted Genes and Dwarfed Plastome in Mycoheterotrophic Sciaphila thaidanica (Triuridaceae, Pandanales). (16th March 2018) - Petersen, Gitte; Zervas, Athanasios; Pedersen, Henrik Æ; Seberg, Ole
Abstract: With a reduced need for photosynthesis, the plastome of parasitic and mycoheterotrophic plants degrades. In the tiny, fully mycoheterotrophic plant Sciaphila thaidanica, we find one of the smallest plastomes yet encountered. Its size is just 12, 780 bp and it contains only 20 potentially functional housekeeping genes. Thus S. thaidanica fits the proposed model of gene loss in achlorophyllous plants. The most astonishing feature of the plastome is its extremely compact nature, with more than half of the genes having overlapping reading frames. Additionally, intergenic sequences have been reduced to a bare minimum, and the retained genes have been reduced in length both compared with the orthologous genes in another mycoheterotrophic species of Sciaphila and in the autotrophic relative Carludovica .